Boron Isotope Geochemistry of the Lakkor Co Salt Lake (Tibet) and Its Geological Significance. (22nd June 2022) - Li, B. K.; Cheng, H. D.; Ma, H. Z.
Abstract : The origin of boron in modern salt lakes has long been a controversial subject. This study focuses on the boron geochemistry of Lakkor Co salt lake, located on the Shiquanhe-Lakkor Co-Yongzhu-Jiali Ophiolite Mélange Zone (SYMZ). Lakkor Co is one of the main boron-rich salt lakes in the Tibetan plateau where the boron concentration ranges from 401 to 849 mg L -1 . The boron isotope value (δ 11 B ) of the carbonate deposit within the Lakkor Co region is -28.08‰. The boron isotope value of the Somme river decreases from -9.97‰ to -11.15‰ after it flows through the carbonate deposit region, indicating that the carbonate deposit in this region releases boron, which has a more negative isotope value. However, the boron isotope value of Bai Kok river increases from -15.63‰ to -13.76‰, when it flows through the Quaternary clay region in Ganga Co, indicating that the carbonate deposit undergoes a process of boron adsorption. It can be concluded that the Quaternary carbonate deposits may be a source of boron and also serve as a temporary boron reservoir, thus playing an important role in the formation of modern salt lake boron deposits in Tibet.